Real-time PCR quantification of spliced X-box binding protein 1 (XBP1) using a universal primer method. - Seung-Bin Yoon (PLoS ONE, 2019)
X-box binding protein 1 (XBP1) mRNA processing plays a crucial role in the unfolded protein response (UPR), which is activated in response to endoplasmic reticulum (ER) stress. Upon accumulation of the UPR-converted XBP1 mRNA splicing from an unspliced (u) XBP1 (inactive) isoform to the spliced (s) XBP1 (active) isoform, inositol-requiring enzyme 1 α (IRE1α) removes a 26-nucleotide intron from uXBP1 mRNA. Recent studies have reported the assessment of ER stress by examining the ratio of sXBP1 to uXBP1 mRNA (s/uXBP1 ratio) via densitometric analysis of PCR bands relative to increased levels of sXBP1 to uXBP1 using a housekeeping gene for normalization. However, this measurement is visualized by gel electrophoresis, making it very difficult to quantify differences between the two XBP1 bands and complicating data interpretation. Moreover, most commonly used housekeeping genes display an unacceptably high variable expression pattern of the s/uXBP1 ratio under different experimental conditions, such as various phases of development and different cell types, limiting their use as internal controls. For a more quantitative determination of XBP1 splicing activity, we measured the expression levels of total XBP1 (tXBP1: common region of s/uXBP1) and sXBP1 via real-time PCR using specific primer sets. We also designed universal real-time PCR primer sets capable of amplifying a portion of each u/s/tXBP1 mRNA that is highly conserved in eukaryotes, including humans, monkeys, cows, pigs, and mice. Therefore, we provide a more convenient and easily approachable quantitative real-time PCR method that can be used in various research fields to assess ER stress.